Stress and Coping Predicts Adjustment and Glycemic Control in Adolescents with Type 1 Diabetes. Issue 1 (5th August 2016) - Jaser, Sarah S.; Patel, Niral; Xu, Meng; Tamborlane, William V.; Grey, Margaret
Abstract: Background: Adolescents with type 1 diabetes are at increased risk for deteriorating glycemic control, poor quality of life, and depressive symptoms. Stress and coping are related to these outcomes in adolescents with diabetes, yet few studies have examined these constructs longitudinally. Purpose: This study aimed to describe stress and coping in adolescents with type 1 diabetes and to examine coping strategies as predictors of adolescent adjustment (i.e., depressive symptoms, quality of life) and glycemic control. Methods: Adolescents with type 1 diabetes completed measures of diabetes-related stress, coping, symptoms of depression, and quality of life at baseline, 6 months, and 12 months. Data on glycemic control were collected from the adolescents' medical charts. Results: The adolescents' use of primary control coping (e.g., problem solving) and secondary control engagement coping (e.g., positive thinking) strategies predicted significantly fewer problems with quality of life and fewer depressive symptoms over time. In contrast, the use of disengagement coping strategies (e.g., avoidance) predicted more problems with quality of life and depressive symptoms. Coping was not a significant predictor of glycemic control. Coping mediated the effects of diabetes-related stress on depressive symptoms and quality of life. Conclusions: The ways in which adolescents with type 1 diabetes cope with diabetes-related stress predict quality of life and symptoms of depression but not glycemic control. Through the use of screening to identify adolescent's diabetes-related stress and targeted interventions to improve coping strategies, there is potential to improve outcomes.